In-situ Self-Assembly of Graphene Supported MnO2 Nanowires for Enhanced Water Oxidation in Both Alkaline and Neutral Solutions - Yuan, Weiyong; Jiang, San ping (The Electrochemical Society, 2013)
The sluggish water oxidation reaction represents a significant challenge in water splitting for energy storage using hydrogen. We herein reported a graphene supported MnO2 nanowires with an ultrasmall diameter and ultrahigh aspect ratio using a novel in-situ self-assembly approach. This nanostructure was investigated as water oxidation catalysts, showing an ultrahigh catalytic activity and good durability in both alkaline and neutral conditions.